National identity change: the case of Lithuanian pupils - Garšvė, Lina (Socialinė teorija, empirija, politika ir praktika, 2013)
SummaryIn this paper, we analyze the national identity of Lithuanian pupils. The theories of national identity change are discussed in the first part of the paper. The second part of the paper is devoted to the analsis of data of a qualitative research. The analysis reveals a shift of national identity and the existence of a complex identity. As a solution to the problems of complex identity, a hermeneutic class as a tool is proposed.Key words: national identity, Lithuanian pupils, hermeneutic class.